2019
DOI: 10.1080/13617672.2019.1618151
|View full text |Cite
|
Sign up to set email alerts
|

Moral conflicts in Iranian secondary schools

Abstract: This article examines moral conflicts identified by students (N = 302) and teachers (N = 20) in the context of Iranian schools. The data were gathered in 2016 fromtwo lower secondary schools in Tehran, one for girls and one for boys. The content analysis of students' essays and teachers' interviews reveal that moral conflicts in Iranian secondary schools have four main themes: 1. Matters related to Staff's behaviour, 2. Matters related to Students' behaviour, 3. Sensitive issues, and 4. Matters related to Pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
3
0
5
Order By: Relevance
“…Indeed, as the present participants viewed it, most Iranian schools do not have a formal policy to forbid physical punishment and violence. The results of a study entitled as “Moral conflicts in Iranian secondary schools” also showed that physical punishment is a common and acceptable disciplinary procedure in Iranian schools [ 21 ]. In this study, moral conflicts in Iranian secondary schools were examined based on essays and interviews with students and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, as the present participants viewed it, most Iranian schools do not have a formal policy to forbid physical punishment and violence. The results of a study entitled as “Moral conflicts in Iranian secondary schools” also showed that physical punishment is a common and acceptable disciplinary procedure in Iranian schools [ 21 ]. In this study, moral conflicts in Iranian secondary schools were examined based on essays and interviews with students and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Hashemi and Ghorbanalızadeh (2015) reported that the ideological values in the Iranian social studies textbooks focused mostly (50.81%) on the formation of national identity. This trend results in people developing an attitude, which warrants further research at different levels (Hedayati et al, 2017b(Hedayati et al, , 2019Shorehkandi and Aliasgari, 2017).…”
Section: Conclusion and Recommendationmentioning
confidence: 90%
“…Pandangan ini berpotensi saling bertentangan dan menciptakan konflik (Koc & Buzzelli, 2016). Dalam konteks sekolah, Ehrich et al dalam Hedayati (2019) menyebutkan bahwa guru sering mengalami konflik moral dalam proses pembelajaran. Konflik yang mengharuskan guru untuk tetap memmbuat keputusan yang benar, meskipun dalam situasi yang sering meragukan bagi guru Sebagai bagian implementasi kurikulum merdeka, pembelajaran berbasis proyek di PAUD telah banyak diminati dan dikaji.…”
Section: Pendahuluanunclassified
“…Lebih khusus lagi, belum ada penelitian pada topik konflik moral guru dalam kaitannya dengan pelaksanaan pembelajaran berbasis proyek. Penelitian-penelitian sebelumnya juga menyatakan bahwa, guru-guru belum disiapkan dengan baik untuk menyelesaikan konflik moral yang terjadi pada konteks sekolah (Hedayati et al, 2019). Sejauh ini, para peneliti di Indonesia menitikberatkan pada manfaat pembelajaran berbasis proyek bagi anak, misalnya untuk menumbuhkan sikap peduli (Suminar et al, 2022), keterampilan sosial (Mala & Hatiningsih, 2022), motorik halus (Sari, 2021), atau kemampuan kerjasama (Dewi et al, 2018).…”
Section: Pendahuluanunclassified